Community Participation in the Development of Ketapang Urban Aquaculture (KUA), Tangerang Regency, Banten Province (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study examines community participation in the development of the Ketapang Urban Aquaculture (KUA) tourism area. Initially, this area was a poor and densely populated settlement with traditional fish ponds as the main source of livelihood. The area was revitalized through an urban aquaculture program, reorganizing residential zones, maintaining local economic activities, and converting unproductive ponds into mangrove gardens to support sustainable tourism. Using a descriptive quantitative method, data were collected from 98 residents via structured questionnaires to assess the level, pattern, and intensity of participation. Results show that 49% of respondents are at the therapeutic participation level, reflecting formal involvement with limited influence on decision-making. Despite this, the community has initiated businesses around KUA, including accommodation, culinary services, handicrafts, and fishery-based products. This study’s novelty lies in demonstrating how local initiatives can drive tourism development and economic opportunities even under limited formal authority. Findings provide guidance for enhancing collaboration between management and residents, building local capacity, and designing inclusive participatory strategies. Strengthening community involvement is vital for sustainable tourism, fostering local entrepreneurship, and promoting ownership and collective responsibility in the KUA area.